2012
DOI: 10.5897/ajb12.236
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of eight plants consumed by great apes in Côte d’Ivoire.

Abstract: Oxidative stress is an aggravating factor involved in a number of pathologies. The source and mobilization of antioxidant compounds are a challenge for the public health sector and new approaches are needed to assess and identify the main sources of antioxidants. Monkeys and great apes are considered to tolerate the Simian immunodeficiency virus (SIV) infection and other diseases. The current study aimed at screening wild chimpanzee's diet to select plants with high antioxidant potential as supplement for impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Tis observation was starkly diferent from the one done by Daniel and Dluya [46] in which they demonstrated that the methanolic stem bark extract of F. sycomorus had a higher ferric reducing power than ascorbic acid (reference drug) which could be the case of diferent solvents used. Nevertheless, the fndings correlate with one done by Ahoua et al [87] on eight diferent Ficus species and it was noted that the majority had signifcantly lower reducing power against the ascorbic acid.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Tis observation was starkly diferent from the one done by Daniel and Dluya [46] in which they demonstrated that the methanolic stem bark extract of F. sycomorus had a higher ferric reducing power than ascorbic acid (reference drug) which could be the case of diferent solvents used. Nevertheless, the fndings correlate with one done by Ahoua et al [87] on eight diferent Ficus species and it was noted that the majority had signifcantly lower reducing power against the ascorbic acid.…”
Section: Discussionsupporting
confidence: 82%
“…Te dose-dependent activities of both extracts showed that an increase in the concentration of the extract increased the levels of bioactive antioxidant compounds [86]. Similarly, studies conducted on diferent Ficus species by Ahoua et al reported the species exhibit strong hydrogen peroxide antioxidant activity in a dose-dependent manner [87]. Te strong scavenging potential of the extracts is refected in their low IC 50 value.…”
Section: Discussionmentioning
confidence: 89%